Effect of dietary omega-3 polyunsaturated fatty acids supplementation of Astyanax lacustris males on semen quality - Carneiro-Leite, Laicia [UNESP]; da Silva, Lorena Pacheco [UNESP]; Pazzini, Hellen Buzollo; Lobato, Stella Indira Rocha [UNESP]; Borges, Laís Pedroso [UNESP]; Reis, Yasmin dos Santos [UNESP]; Gomes-Silva, Luciane [UNESP]; Ribeiro, Cristiéle da Silva [UNESP]; Veríssimo-Silveira, Rosicleire [UNESP]; Ninhaus-Silveira, Alexandre [UNESP] (FapUNIFESP (SciELO), 2023)
This study aimed to verify whether the inclusion of omega-3 polyunsaturated fatty acids (PUFAs-ô3) in the diet of Astyanax lacustris males improves seminal quality. Four hundred fish were arranged in 20 boxes of 180 L in the recirculation system. These were fed with isoprotein diets (32% CP), until apparent satiation, with four levels of marine fish oil rich in PUFAs-ô3 inclusion (In% = 0, 3, 6, and 9), for 105 days. After, males were hormonally induced to spermiation, and semen was collected after 226 ATUs. Parameters evaluated were osmolality, seminal volume and color, spermatic concentration, sperm morphology, membrane integrity and, sperm motility (total and progressive motility, velocity curvilinear, straight line and average path, linearity and rectilinearity coefficients, trajectory oscillation, head lateral displacement amplitude, and cross-beat frequency). Seminal volume was greater in the In-0 and In-3 groups. Inclusion of PUFAs-ô3 positively influenced the kinetic parameters, as treatment with 6% and 9% of inclusion fish oil resulted in higher values for most of these parameters and did not differ statistically from each other. Thus, it is concluded that the addition of PUFAs-ô3 to the feed of breeders significantly improved the seminal quality of A. lacustris males.
Keywords: Fish sperm; Marine fish oil; Reproduction; Yellowtail lambari